On the brain struggles to recognize basic facial emotions with face masks: an fMRI study - Abutalebi, Jubin; Gallo, Federico; Fedeli, Davide; Houdayer, Elise; Zangrillo, Federica; Emedoli, Daniele; Spina, Alfio; Bellini, Camilla; Del Maschio, Nicola; Iannaccone, Sandro; Alemanno, Federica (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic impacted public health and our lifestyles, leading to new social adaptations such as quarantine, social distancing, and facial masks. Face masks, covering extended facial zones, hamper our ability to extract relevant socio-emotional information from others’ faces. In this fMRI study, we investigated how face masks interfere with facial emotion recognition, focusing on brain responses and connectivity patterns as a function of the presence of a face mask. Methods A total of 25 healthy participants (13F; mean age: 32.64 ± 7.24y; mean education: 18.28 ± 1.31y) were included. Participants underwent task-related fMRI during the presentation of images of faces expressing basic emotions (joy or fear versus neutral expression). Half of the faces were covered by a face mask. Subjects had to recognize the facial emotion (masked or unmasked). FMRI whole-brain and regions-of-interest analyses were performed, as well as psychophysiological interaction analysis (PPI). Results Subjects recognized better and faster emotions on unmasked faces. FMRI analyses showed that masked faces induced a stronger activation of a right occipito-temporal cluster, including the fusiform gyrus and the occipital face area bilaterally. The same activation pattern was found for the neutral masked > neutral unmasked contrast. PPI analyses of the masked > unmasked contrast showed, in the right occipital face area, a stronger correlation with the left superior frontal gyrus, left precentral gyrus, left superior parietal lobe, and the right supramarginal gyrus. Discussion Our study showed how our brain differentially struggles to recognize face-masked basic emotions, implementing more neural resources to correctly categorize those incomplete facial expressions.